From frustration to coping with caring for death by nurse technicians - Beraldo, Livia Maria [UNESP]; Almeida, Debora Vieira de [UNESP]; Mangini Bocchi, Silvia Cristina [UNESP] (Assoc Brasileira Enfermagem, 2015)
Objective: to understand nurse technicians' experience with caring for the death of terminal patients in ICUs and to configure a theoretical model. Method: qualitative study with theoretical saturation when analyzing the 10th non-directive interview, having as reference Grounded Theory, Symbolic Interactionism and Bioethics. Results: the core category - from frustration to coping with dignified nursing care for finitude: the acceptance of death as a therapeutic and intervenient component - emerged from the comparison of the sub-processes: when the nurse does not feel prepared for caring for death, accepting death as a therapeutic phenomenon and developing coping strategies. Conclusion: according to Symbolic Interactionism, a novice professional's frustration in caring for an individual for death is related to his/her interaction and interpretation of the situation as he/she feels prepared only to care for individuals for life.
Keywords: Death; Nursing Care; Intensive Care Units